(untitled) (International Research in Economics and Finance, 2022)
The rapid development of financial technology has brought about a significant impact on China’s financial services. The development of innovative technologies based on big data, cloud computing, Internet of Things, artificial intelligence and other technologies has played a positive role in improving the overall efficiency of China’s modern financial system, but it is also accompanied by some risks. How to prevent the risk of financial technology development, improve financial technology innovation, and develop the real economy is a serious problem facing China’s financial regulatory authorities. This paper analyzes the development status and trends of financial technology and the risks faced by the development of financial technology, and puts forward corresponding regulatory policies.